Simulation, design, and characterization of electrically-pumped VECSELs for future passive modelocking - Hoffmann, M.; Barbarin, Y.; Pallmann, W. P.; Maas, D. J.H.C.; Kreuter, P.; Witzigmann, Bernd; Golling, M.; Südmeyer, T.; Keller, U. (Optics InfoBase Conference Papers, 2010)
An ultrafast electrically-pumped VECSEL design requires an acceptable trade-off in cw output power. Validating our design guidelines and simulations 120 mW cw output power are generated. Homogenous current injection is even achieved for large devices. © 2009 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-11